A Second PDZ-Containing Serine Protease Contributes to Activation of the Sporulation Transcription Factor σ(K) in Bacillus subtilis - Pan, Qi (American Society for Microbiology, 2003)
Gene expression late during the process of sporulation in Bacillus subtilis is governed by a multistep, signal transduction pathway involving the transcription factor σ(K), which is derived by regulated proteolysis from the inactive proprotein pro-σ(K). Processing of pro-σ(K) is triggered by a signaling protein known as SpoIVB, a serine protease that contains a region with similarity to the PDZ family of protein-protein interaction domains. Here we report the discovery of a second PDZ-containing serine protease called CtpB that contributes to the activation of the pro-σ(K) processing pathway. CtpB is a sporulation-specific, carboxyl-terminal processing protease and shares several features with SpoIVB. We propose that CtpB acts to fine-tune the regulation of pro-σ(K) processing, and we discuss possible models by which CtpB influences the σ(K) activation pathway.